Gold nano particles for use in therapeutic methods - Abdullah, Syahrilnizam; Dorasamy, Dhayanand; Rosli, Rozita (2012)

(untitled)
The invention provides a method for cell or tissue destruction using thermal energy, in particular fat cells, for therapeutic or cosmetic purposes. The invention provides method for inducing cell lysis wherein the steps includes (a) administering gold nanoparticle to the cells; (b) exposing the gold nanoparticles to a radiation source; and (c) destroying the cells using the radiation exposed gold nanoparticle, wherein the gold nanoparticle does not attach to the cells and emits heat for cell destruction when exposed to radiation. The gold nanoparticles emit heat due to electron oscillation and the electron oscillation is produced by interacting electrons surrounding the gold nanoparticles with photons from the radiation. The radiation source is a photonic radiation which includes near-infrared. The method is not only applicable to fat cells in particular but also cells or tissues such as connective tissue, nerve cells and blood vessels.